Wzrost szczepów wiązu górskiego (Ulmus glabra Huds.) w archiwum klonów w Nadleśnictwie Bielsk - Mioduszewski, Sławomir; Korczyk, Adolf (Leśne Prace Badawcze, 2013)
Vegetative progeny were obtained from 46 elms (Ulmus glabra Huds.) by grafting. These grafted trees were planted in 2009 in a clone archive in forest plot 264j in the Bielsk Forest District. After one year of growth, elm clone survival ranged from 38% to 100% (89% on average). Although all clones were of similar age and were grown under similar conditions, their average height was highly variable and ranged from 99.0 cm (clone no. 9473z) to 186.6 cm (clone no. 9645z), while average root collar diameter ranged from 8.4mm (clone no. 9473z) to 18.0 mm (clone no. 9645z). There were large differences crown architectural among the different clones, and variation in average shape of the crown was high (from 2.6 in clone no. 9655 to 3.8 in clone no. 9446z). Index breeding values determined on the standardized data for height, root collar diameter, crown shape and survival, ranged from -0.71 (clone no. 9473z) to 0.61 (clone no. 9645z). Clones from Czerwony Dwór reached a better breeding value (0.17) than clones from Gołdap (-0.0266), and variation in their average breeding values was high (0.197).